Sulfonated Magnetic Nanoparticles as Recyclable Catalyst for Facile One-Pot Green Synthesis of 3,4-Dihydro-2H-indazolo[1,2-b]phthalazine-1,6,11(13H)-trione Derivatives - Mohammad Reza Zare; Davood Azarifar; Omolbanin Badalkhani; Mehdi Jaymand (Iranian Journal of Chemistry & Chemical Engineering, 2020)
Sulfonated magnetic nanoparticles (SO3H-Fe3O4@SiO2 MNPs) have been explored as an efficient, cost-effective, and recyclable nanocatalyst for the facile synthesis of 3,4-dihydro-2H-indazolo[1,2-b]phthalazin-1,6,11(13H)-triones through a one-pot three-component reaction between aldehydes, dimedone, and phthalhydrazide under mild and green (solvent-free) conditions. Simple separation of the catalyst using an external magnet, efficient recyclability of the developed magnetic nanocatalyst up to five fresh runs without significant loss in its catalytic activity, excellent yields of the designed reactions (88 to 98%), low reaction times as well as solvent-free and facial reaction condition are some advantages of the present procedure that qualified the fabricated magnetic nanocatalyst for industrial applications.